2012
DOI: 10.1007/s00404-012-2624-8
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid for cesarean section: a double-blind, placebo-controlled, randomized clinical trial

Abstract: This study confirms that tranexamic acid is effective in reducing intrapartum and postpartum bleeding in patients giving birth by cesarean section. Although some obstetricians are still worried about its thrombosis risk, our study shows that it can be used safely in aforementioned patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
85
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 23 publications
9
85
0
5
Order By: Relevance
“…15 A reduction in postoperative bleeding of around 17% at 2 hours was found in the intervention group, which was significantly less than the almost 25% in IV group tranexamic acid and 23% reduction topical tranexamic group in postoperative blood loss found in the present study Aleem A et al in double blind case control trial who conduct their work upon 740 patients and concluded that the use of tranexamic acid before elective cesarean section is associated with reduced post-partum hemorrhage during and pot elective cesarean section. 16 Also, present results were in agreement with Ahmed et al, Movafegh et al, Goswam et al and Senturk et al [20][21][22][23] The topical tranexamic group demonstrated that topical administration of 2 gm of tranexamic acid in in 2000 ml normal saline at placental bed and uterine scar at cesarean delivery reduced intra-and postoperative blood loss, as well as the amount of intraoperative oxytocin used. Hemoglobin level showed a non-significant r decrease in the control group There was no study in the literature address the role of topical tranexamic acid during cesarean section although Two case reports on the use of topical tranexamic acid to control postoperative local bleeding in 2 women with clotting disorders who were undergoing gynecologic procedures.…”
Section: Discussionsupporting
confidence: 82%
“…15 A reduction in postoperative bleeding of around 17% at 2 hours was found in the intervention group, which was significantly less than the almost 25% in IV group tranexamic acid and 23% reduction topical tranexamic group in postoperative blood loss found in the present study Aleem A et al in double blind case control trial who conduct their work upon 740 patients and concluded that the use of tranexamic acid before elective cesarean section is associated with reduced post-partum hemorrhage during and pot elective cesarean section. 16 Also, present results were in agreement with Ahmed et al, Movafegh et al, Goswam et al and Senturk et al [20][21][22][23] The topical tranexamic group demonstrated that topical administration of 2 gm of tranexamic acid in in 2000 ml normal saline at placental bed and uterine scar at cesarean delivery reduced intra-and postoperative blood loss, as well as the amount of intraoperative oxytocin used. Hemoglobin level showed a non-significant r decrease in the control group There was no study in the literature address the role of topical tranexamic acid during cesarean section although Two case reports on the use of topical tranexamic acid to control postoperative local bleeding in 2 women with clotting disorders who were undergoing gynecologic procedures.…”
Section: Discussionsupporting
confidence: 82%
“…In another study, Shahid A and Khan A [27] while determining the effectiveness of tranexamic acid (TXA) in reducing blood loss during and after caesarean section (CS), the increased in the risk of thrombosis was not reported. Similar studies by Sentürk MB et al [28] in 220 patients and Gungorduk K et al [29] in 660 patients, the incidence of thromboembolic events were not increased.…”
Section: Discussionsupporting
confidence: 79%
“…Sentürk et al [32] used TXA 20 cc injected 10 min before the start of CS and found TXA reduced intraoperative and postoperative blood loss without concomitant complications caused by TA such as venous thromboembolism, gastrointestinal problems…”
Section: Resultsmentioning
confidence: 99%